Odpowiedź :
Zad 1
a) -2x + (-6xy + 4x - y) = -2x - 6xy + 4x - y = 2x - 6x - y
b) k - (- 2k + 8m - 3km) = k + 2k - 8m + 3km = 3k - 8m + 3km
c) -6xy - (2xy - 3x + 4y) = -6xy -2x + 3x - 4y = -6xy + x - 4y
d) 9a + 4c - (8c - 2a) = 9a + 4c - 8c + 2a = 11a - 4c
e) -(-3t + w) - (t - 2w) = 3t - w - t + 2w = 2t + w
f) -(3x + 1) + (6x + 2) = -3x - 1 + 6x + 2 = 3x + 1
Zad 2
a) (4pr - p + 3) + (-pr - p - 8) = 4pr - p + 3 - pr - p - 8 = 3pr - 2p - 5
b) -(5xy - x + 8) + (6 - 3x + xy) = -xy + x - 8 + 6 - 3x + xy = -2x - 2
c) (2a + 3b - 4c + 5d) - (a - 7b + 2c - 6d) = 2a + 3b - 4c + 5d - a + 7b - 2c + 6d =
= a + 10b - 6c + 11d
d) -([tex]x^{2}[/tex] + c + 2) - (- [tex]x^{2}[/tex] + x - 1) + (- [tex]x^{2}[/tex] - x - 1) = -[tex]x^{2}[/tex] - c - 2 + [tex]x^{2}[/tex] - x + 1 - [tex]x^{2}[/tex] - x - 1 =
= -[tex]x^{2}[/tex] - c - 2x - 2
Zad 3
2(3x - 8y + 0,5) = 6x -16y + 1
Odpowiedź: D
Zad 4
a) 4(2x - 6y + 9) = 8x -24y + 36
b) (-5a - 2b - 1)8 = -40a - 16b - 8
c) (1 - 3k - 4[tex]k^{2}[/tex])6 = 6 - 18k - 24[tex]k^{2}[/tex]
d) 6([tex]\frac{1}{3}[/tex]k + [tex]\frac{1}{2}[/tex]l - [tex]\frac{1}{6}[/tex]m) = 2k + 3l - m
e) [tex]\frac{3}{4}[/tex](20[tex]p^{2}[/tex] - 4p + 16) = 15[tex]p^{2}[/tex] - 3p + 12
f) ([tex]\frac{1}{3}[/tex][tex]m^{2}[/tex] - [tex]\frac{1}{4}[/tex]m + [tex]\frac{1}{3}[/tex])60 = 20[tex]m^{2}[/tex] - 15m + 20
g) (40x - 200xy + 80[tex]y^{2}[/tex]) - 0,1 = 4x - 20xy + 8[tex]y^{2}[/tex]
h) 0,4([tex]\frac{1}{4}[/tex][tex]a^{3}[/tex] + [tex]\frac{1}{2}[/tex][tex]a^{2}[/tex] - [tex]\frac{3}{4}[/tex]a) = 0,1[tex]a^{3}[/tex] + 0,2[tex]a^{2}[/tex] - 0,3a
Zad 7
Pierwsza rubryka
-1(x - y + 4) = -x + y - 4 Fałsz
Druga rubryka
-(4 - 5x + 6y) = -4 + 5x - 6y Prawda
Trzecia rubryka
(-6 -4a + c)(-1) = 6 + 4a - c Prawda